Recombinant plasmid that carries part of the nitrogen fixation (nif) gene cluster of Klebsiella pneumoniae. - Cannon, F C (1977)
We have cloned fragments of the Klebsiella pneumoniae genome that carry part of the his operon and part of the nitrogen fixation (nif) gene cluster on the amplifiable plasmid pMB9. One particular plasmid, pCRA37, complements mutations in the hisD, nifB, and nifF loci. The physical map of pCRA37 as determined by restriction enzyme analysis correlates with the genetic map of the his-nif region as determined previously by phage P1-mediated cotransductional analysis.